Relationship between Social Media and Employees Job Performance: Mediating Role of Job Engagement - Arshad, Adnan; Raheed, Rabia (South Asian Review of Business and Administrative Studies (SABAS), 2020)
Social media usage, if out of context and non-work related and only for personal use, becomes an addiction along with information overload is considered as an integral part. Success and failure the work have and motivation of an employee at the workplace which in turn affects the job performance of employees negatively. In our study, we have tried to analyze internal and external contingent factors that affect the use of Social media. Our study has utilized contingent factors perceived SM Addiction, Perceived Information overload, and Cognitive Fatigue. We have used survey-based research. Data collected through an online questionnaire along with Public sectors. We collected data of 173.By using conservation of resource theory Results depict that perceived information overload and SM addiction have significant relation on Social Media. This shows that the external contingent factor has stronger relation to SM Adoption in Social Media. Imperative data on the relationship shared by the SMA, CF, and IOL with job performance within the sight of job engagement. Social Media are significant for survival. The primary target of this examination is to look at the relation s of social media usage also its effect on an individual’s performance on the job. To uncover this, we need to look upon the theory of conservation of resources which implicates that the employees are proactive in conserving their resources that helps them in performing their day to day task, whether it be a work environment, tools used for task performance or personal energy.